Methodical features of teaching to the selfmassage and оne other massage in the complex of facilities of increase of adaptation possibilities of organism of students - Каніщева [Kanishcheva O.], О. П. (Slobozhanskyi Herald of Science and Sport, 2013)
<!--[if gte mso 9]> Normal 0 false false false RU X-NONE X-NONE MicrosoftInternetExplorer4 <![endif]--> The problem of increase of amount of students is in-process examined being in the pre-nosology state of organism the index of which is a level of adaptation possibilities of organism of students. The necessity of the differentiated going is specified near the increase of level of these possibilities. A massage exudes between existent effective facilities of improvement of the state of their organism. The purpose of work was to find the methods of the rapid mastering students this procedure within the framework of educational process on physical education. In the process of study of literary sources the integral method of teaching, which allowed quickly to learn to execute a massage on itself or on whom or, was distinguished. As addition application of mechanical massagers is recommended. The conducted questioning of students specified on the improvement of their capacity during an educational day. <!--[if gte mso 9]> <![endif]--><!--[if gte mso 10]> <![endif]-->